Sistem Peringatan Dini Menggunakan Masker Ketika Keluar Rumah Berbasis Android - Ivan Febrianda; Khozainuz Zuhri; Yodhi Yuniarthe (Jurnal Teknologi dan Informatika (JEDA), 2022)
we often call the corona virus. The spread of this virus is very fast and has various methods of spreading, one of which is by touching the virus directly from exposed humans. There are several efforts to prevent the spread of the virus, such as implementing physical distancing, washing hands with soap, using masks, covering your mouth when sneezing or coughing and trying to stay at home. One of the prevention efforts that can be done is to use a mask covering the nose and mouth, but sometimes we often forget to wear a mask when leaving the house. To minimize this the author has the initiative to create an early warning system using masks when leaving the house on an android smartphone. In making a warning system using a mask by preparing a Wemos D1 Mini as a wifi signal transmitter and an android smartphone equipped with a notification or warning system. A notification will notify you when the distance between devices exceeds the system preset. In detecting the distance between devices, it is strongly influenced by the environment such as the room or outdoors, the signal will be stronger when outdoors than in an insulated room.